2020
DOI: 10.1519/jsc.0000000000003702
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysiological Stress Markers During Preseason Among Elite Female Soccer Players

Abstract: This study aimed to investigate changes and correlations between mood states and various physiological stress markers after a 7-week preseason period among elite female soccer players. Twenty-four elite female soccer players participated in this study (26.4 6 3.7 years). Their internal training load, mood states, day and evening salivary testosterone and cortisol concentrations, blood creatine kinase concentration (CK), and heart rate variability (HRV) were assessed during the first week of preseason (PRE), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…The present study revealed that there were no significant changes in the T/C ratio after the pre-season training period. This result was supported by a previous study that showed that no significant changes in the T/C ratio after intense pre-season traninig in soccer players [ 88 ], and non-athletic men [ 83 ]. Contrary to our findings, recent studies observed significant reductions in the T/C ratio in response to a high volume of training sessions [ 39 , 89 ], and a period of congested match play [ 86 , 89 ] in professional soccer players.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The present study revealed that there were no significant changes in the T/C ratio after the pre-season training period. This result was supported by a previous study that showed that no significant changes in the T/C ratio after intense pre-season traninig in soccer players [ 88 ], and non-athletic men [ 83 ]. Contrary to our findings, recent studies observed significant reductions in the T/C ratio in response to a high volume of training sessions [ 39 , 89 ], and a period of congested match play [ 86 , 89 ] in professional soccer players.…”
Section: Discussionsupporting
confidence: 84%
“…Additionally, our result was not similar to previous studies that reported that the T/C ratio increased significantly in team sports athletes after the pre-season period [ 81 , 84 , 85 , 89 ]. As in the present study, Botelho et al [ 88 ] stated that a significantly unchanged T/C ratio after the pre-season period was associated with a favorable response to the training load, and adequate coping with training stresses. The current study revealed that the T/C ratio, which did not change significantly, and the conversely significant increases in cortisol and testosterone, after the pre-season could be explained by an environment that reflects a dynamic hemostatic balance between an anabolic and catabolic process in muscle [ 81 , 83 ].…”
Section: Discussionsupporting
confidence: 75%
“…Among the mood subscales, fatigue and depression were sensitive to increased training load. Moreover, female soccer players reported significantly more tension, depression, anger, fatigue, confusion, and total mood disturbance after 7 weeks of intensive training [ 37 ]. In the present study, the lack of change in the depression subscale may have been due to the age of the participants (youth compared to adults in previous studies), or the relatively short duration of the intense training camp (one week).…”
Section: Discussionmentioning
confidence: 99%
“…Also, cortisol and testosterone are hormonal parameters associated with psychophysiological stress. Recent studies revealed that cortisol and testosterone were frequently used in the evaluation of anabolic and catabolic balance [ 57 60 ]. The previous studies showed that the intensification of training demands in the PS phase seem to exert a significant catabolic environment, which translates to a raise of cortisol and reduction in the testosterone [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%